Characterization of subsurface fluxes at the plot scale during flash floods in the Valescure catchment, France. Issue 4 (15th April 2021) - Bouvier, Christophe; Adamovic, Marko; Ayral, Pierre‐Alain; Brunet, Pascal; Didon‐Lescot, Jean‐François; Domergue, Jean‐Marc; Spinelli, Rosario
Abstract: This study focuses on a 10‐m 2 plot within a granitic hillslope in Cevennes mountainous area in France, in order to study infiltration and subsurface hydrological processes during heavy rainfalls and flash floods. The monitoring device included water content at several depths (0–70 cm for the shallow soil water; 0–10 m for the deep water) during both intense artificial and natural rainfall events, chemical and physical tracers, time‐lapse electrical resistivity tomography. During the most intense events, the infiltrated water was estimated to be some hundreds of millimetres, which largely exceeds the topsoil capacity (≤40 cm deep in most of the cases). The weathered/fractured rock area below the soil clearly has an active role in the water storage and sub‐surface flow dynamics. Vertical flow was dominant in the first 0–10 m, and lateral flow was effective at 8–10 m depth, at the top of the saturated area. The speed of the vertical flow was estimated between 1 and 10 m/hr, whereas it was estimated between 0.1 and 1 m/hr for the lateral flow. The interpretation of the experiments might lead to a local pattern of the 2D‐hydrological processes and profile properties, which could be generic for most of the mountainous catchments under Mediterranean climate. It suggests that fast triggering of floods at the catchment scale cannot be explained by a mass transfer within the hillslope, but should be due to a pressure wave propagation through the bedrock fractures, which allows exfiltration of the water downstream the hillslope. Abstract : Our plot experiment was dedicated to characterize depths and velocities of both vertical/lateral subsurface fluxes along steep slopes of a mountainous Mediterranean catchment. Heavy rainfalls up to several hundreds of millimetres a day were used to be completely infiltrated within the 0–10 m active area, including the thin topsoil layer and the underlaying weathered/fractured area. Due to slow velocities of the lateral fluxes, a piston flow process through the fracturated area is required to explain flash flood triggering at the catchment scale.